DETERMINATION OF INITIAL LAG AND MAXIMUM LAG DISTANCE OF SEMIVARIOGRAM ON RESERVES CALCULATION OF GOLD VEIN - Nur Ali Amri; Abdul Aziz Jemain; Abdul Rauf (Jurnal Teknologi Pertambangan, 2015)
The resources calculation is one of the early stages before the mining operation, which begins with the samples prediction. Ordinary kriging is a part of the kriging method that operated by semivariogram parameters. The calculation of these parameters based on several things, including the determination of lag distance and the fitting model. This paper based on the determination of the maximum lag distance of 500 and 800 where the lag distance for both, respectively 15, 25 and 35 with WLS and OLS fitting models. The six combinations can be concluded that increasing of maximum lag distance adds to a large of sill and extend the range. OK prediction shows that the largest gold grade mean (5.032) occurs in the kriging using WLS fitting models, in which the maximum lag distance semivariogram is 500 and the distance of each lag is 35.Keywords: Lag distance, semivariogram, fitting, kriging. AbstrakPerhitungan sumberdaya merupakan salah satu tahapan awal sebelum operasi pertambangan, yaitu aktivitas yang dimulai dari pensampelan. Ordinary kriging adalah bagian dari metode kriging, yang dapat bekerja dengan parameter utama semivariogram. Perhitungan semivariogram ini didasarkan pada beberapa hal mencakup penentuan jarak lag dan fitting model. Tulisan ini mendasarkan kepada penentuan jarak maksimum lag 500 dan 800, dimana masing-masing jarak lagnya adalah 15, 25 dan 35 dan fitting menggunakan model WLS dan. Enam kombinasi diperoleh, bahwa penurunan jarak lag maksimum berakibat pada penambahan sill dan range. Prediksi OK memperlihatkan bahwa rata-rata grade terbesar adalah 5,032, dan berlaku pada kriging yang menggunakan fitting model WLS,dimana jarak maksimum lag adalah 500 dan jarak masing-masing lag adalah 35.Katakunci: Jarak lag, semivariogram, fitting, kriging.